Upaya Peningkatan Problem Solving Berdasarkan Teori Heller Pada Materi Hukum Pascal di Kelas XI-MIA MAN 2 Bener Meriah - Salwa Aiyesi; Fera Annisa; Fitriyawany (Educator Development Journal, 2023)
Based on the interview that was conducted with Mrs. Kamalia S.Pd. as a teacher in Physics at MAN 2 Bener Meriah it is known that there are still students who find it difficult to solve problems in Pascal's Law material so that Problem Solving skills are needed to solve complex problems. The teacher makes every effort so that students can develop Problem Solving skills through the learning process. This study aims to find out how to improve students' ability to solve problems based on Heller's Theory on Pascal's Law Material in class XI MAN 2 Bener Meriah. The population in this study were all students in class XI and the sample was students in class XI-MIA MAN 2 Bener Meriah. This research method is a quantitative method with a Classroom Action Research (CAR) approach, where the data collection instruments used in this research are teacher and student observation sheets, and test question sheets. Based on the results of the research, it can be seen that in the first cycle the ability of students from the initial pre-test results obtained a percentage of 0% then seen from the post-test results obtained a percentage of 44.4%. However, after evaluating the students' deficiencies and difficulties in understanding the questions, it can be seen in the second cycle of research that the pre-test percentage results were 80% and the post-test results were 100%. The students have been able to complete their studies well. The application of Problem Solving based on Heller's Theory is able to improve problem solving skills and student learning outcomes in class XI MAN 2 Bener Meriah